Projecting Professional Islamic Teachers: Evidence from IAIN Surakarta - Choiriyah, Siti; Kumaidi, Kumaidi; Kartowagiran, Badrun (Dinamika Ilmu, 2018)
This study examines the quality and features associated with studying six study programs. It examines the quality of FITK in IAIN Surakarta with respect to  their readiness to prepare professional teachers to teach students internalized Islamic values.  The methodology adopted in carrying out this research study is the descriptive quantitative with no treatment design using 196 participants. Data was collected using Delta Internal Quality Assurance derived to evaluate Islamic higher education institutions.  The instrument consisted of 10 sets of questionnaires, 7 evaluation dimensions, and 477 questionnaire items.  The results obtained, show that all six study programs receive very good quality in seven dimensions, namely: vision and mission, curriculum, competency of lecturers and staffs, infrastructure and facilities, teaching learning process, student development supervisory, and graduate competency. Similarly, it showed that FITK being the institution’s umbrella, also has good reputation with seven dimension.  From the analysis obtained, both FITK and the six study programs are ready to produce Islamic professional teachers as indicated by the graduate competency.